Admiral Nursing—A Model of Specialist Dementia Care in Acute Hospitals. (August 2020) - Aldridge, Zena; Oliver, Emily; Gardener, Hannah; Dening, Karen Harrison
Introduction: The rising prevalence of dementia has led to increased numbers of people with dementia being admitted to acute hospitals. This demand is set to continue due to an increasingly older population who are likely to have higher levels of dependency, dementia, and comorbidity. If admitted to the hospital, people with dementia are at higher risk of poor outcomes during and following a hospital admission. Yet, there remains a significant lack of specialist support within acute hospitals to support people with dementia, their families and hospital staff. Methods: Admiral Nurses are specialists that work with families affected by dementia and provide consultancy and support to health and social care colleagues to improve the delivery of evidenced based dementia care. Historically, Admiral Nurses have predominantly been based in community settings. In response to the increasing fragmentation of services across the dementia trajectory, the Admiral Nurse model is evolving and adapting to meet the complex needs of families impacted upon by dementia inclusive of acute hospital care. Results: The Admiral Nurse acute hospital model provides specialist interventions which improve staff confidence and competence and enables positive change by improving skills and knowledge in the provision of person-centred dementia care. The role has the capacity to address some of the barriers to delivering person centred dementia care in the acute hospital and contribute to improvements across the hospital both as a result of direct interventions or influencing the practice of others. Conclusion: Improving services for people with dementia and their families requires a whole system approach to enable care coordination and service integration, this must include acute hospital care. The increasing numbers of people with dementia in hospitals, and the detrimental effects of admission, make providing equitable, consistent, safe, quality care and support to people with dementia and their families a national priority requiring immediate investment. The inclusion of Admiral Nursing within acute hospital services supports service and quality improvement which positively impacts upon the experience and outcomes for families affected by dementia.